PENGARUH MACAM DAN WAKTU PEMBERIAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL KEDELAI EDAMAMAE (Glycine max L.) VARIETAS DEGA 1 - Putra Bungsu Siahaan; Djoko Heru Pamungkas; Darnawi (Universitas Sarjanawiyata Tamansiswa, 2026)
This research aims to determine the results of the optimal combination of the effect of the type and time of application of NPK fertilizer on the growth and yield of edamamae soybeans (Glycine max L.) in increasing the growth and production of the Dega 1 variety of edamamae soybeans which was carried out in October- December, at the Integrated Laboratory of the Bachelorwiyata Tamansiswa University. The altitude is 88 meters above sea level (masl), the soil type is regosol, the soil pH is 5.5-7, the average temperature is 26-320C, and the rainfall is 1,654 mm/year. This research is a factorial research prepared using a 3x3 Randomized Block Design (RAK) with 3 replications. The first factor is Nitrogen (N), which consists of 3 levels, namely N1= Phonska: Multipadi, N2= Mutiara:Multipadi, and N3= Yaramila:Multipadi. The second factor is Time of Delivery (W), which consists of 3 levels, namely W1=10 days, W2= 10 and 40 days, and W3= 40 days. The parameters observed were plant height, number of leaves, fresh weight, dry weight, seed weight per plant, number of pods per plant, number of seeds per pod, weight of 100 seeds (g), and weight of soybeans per hectare (tons/ha). There is an interaction between the treatment of giving the type of NPK fertilizer and the time of giving NPK fertilizer, on the weight of seeds per plant. The best combination on the weight of seeds per plant is a mixture treatment of 50% Phonska: 50% Multipadi (N1) with a time of giving 10 & 40 HST (W2).